The prevalence and risk-factors of oral HPV DNA detection among HIV-infected men between men who have sex with men and heterosexual men. Issue 1 (8th January 2021) - Gonçalves, Helena M.; Silva, Jani; Pintado Maury, Inês; Tavares, Ana; Campos, Carla; Sousa, Hugo; Jacinto, Amado; Aguiar, Pedro; Caldeira, Luís; Medeiros, Rui
Abstract: Background: Human papillomavirus (HPV)-associated oropharyngeal carcinomas are becoming more common with epidemiological impact on human immunodeficiency virus (HIV)- positive individuals. Objective: We evaluated prevalence and risk factors for oral HPV DNA among HIV-infected men who have sex with men (MSM) or heterosexual men. Methods: This cross-sectional hospital-based study included 255 HIV-infected men with different sexual orientation 142 MSM and 113 heterosexual men, who answered a self-administered questionnaire on sociodemographic, clinical and behavioural data. Oral swab and mouthwash samples were analysed by polymerase chain reaction and genotyped by Anyplex TM II 28 (Seegene ® ). Results: Oral HPV was detected in 17.6% (95% Confidence Interval (CI) 13.5–22.8%), 17.6% in MSM and 17.7% in heterosexual men ( p  = .984). Multiple HPV infections were detected in 86.7% of HPV-positive men. HPV 56 (13.7%) was the most prevalent high-risk genotype, HPV 66 (7.8%) and HPV 70 (12.3%) were the most prevalent probable HR and low-risk HPV genotypes (12.3% and 7.1%, respectively). At multivariable analysis models, oral HPV was associated with >100 lifetime sexual partners (Odds Ratio (OR) 3.73; 95% CI 1.42–9.77) or lifetime tongue-kissing partners (OR 3.20; 95% CI 1.22–8.39) and lower education level (OR 2.90; 95% CI 1.08–7.78 and 2.74; 95% CI 1.04–7.27, respectively). Conclusions: Oral HPV prevalence was similar between HIV-infected MSM and heterosexual men. Oral HPV was associated with lifetime sexual partners, lifetime tongue-kissing partners and being undergraduate, independently of sexual orientation.